HPW anchored Meso-HZ-5, a novel catalyst for selective synthesis of ethyl levulinate biofuel by alcoholysis of biomass-derived furfuryl alcohol - Nandiwale, Kakasaheb Y.; Pande, Ashwini M.; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2018)
Ethanolysis of biomass derived furfuryl alcohol (FA) produces ethyl levulinate (EL), a biofuel additive and precursor for -valerolactone synthesis. The present study is devoted to develop an efficient and an environmentally benign catalytic system for one-pot conversion of FA to EL biofuel, by revealing an insight of the catalytic mechanism. The catalytic activity of H-ZSM-5, Meso-HZ-5 (desilicated H-ZSM-5) and different percentage H3PW12O40(HPW) anchored to Meso-HZ-5 catalysts have been evaluated for the FA ethanolysis. As per our knowledge, this is the first research reporting the application of HPW anchored to Meso-HZ-5 catalysts for the conversion of FA into EL in biomass utilization. These catalysts were synthesized and characterized by Powder X-ray diffraction (XRD), N-2 physisorption and temperature programmed NH3 desorption (TPAD). Products of FA ethanolysis viz., 4,5,5-triethoxypentan-2-one (TEP), ethoxy-methyl- furan (EMF), diethyl ether (DEE), EL were identified by Gas Chromatography-Mass Spectroscopy (GC-MS) and quantified by flame ionization detector (GC-FID). The physicochemical properties of catalysts were found to correlate to the product distribution matrix. Moreover, influences of several process parameters such as catalyst amount, reactant molar ratio, temperature and time on the extent of FA ethanolysis were systematically investigated. Under optimized conditions, 15% (w/w) HPW/Meso-HZ-5 exhibited a remarkable catalytic performance with complete FA conversion (100%) along with 97% yield of EL, these activity values are superior than the previously reported studies. The present study provides an insight of the catalytic mechanism along with a potential environmental benign and the economic catalyst for the efficient synthesis of EL biofuel from the biomass-derived FA